FAKTOR-FAKTOR YANG MEMPENGARUHI MEKANISME KOPING DENGAN KEPATUHAN MINUM OBAT PADA PENDERITA TUBERCULOSIS - Janter Sumilat, Vervando; Iswati, Ning; Tri Kartika, Agil Putra; Anugrah, Anas Kiki; Edy Santoso, Raden Bagus (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Based on document searches, Puskesmas Meuraxa is one of the Puskesmas with the highest TB cases in Aceh Province. It is known that there were 52 cases of TB during 2022. The purpose of this study was to determine the factors that influence coping mechanisms with adherence to taking medication in patients with tuberculosis. The design of this study was cross sectional. The research time began in November 2022. The sample amounted to 52 people who were collected using random sampling technique. Data analysis used is univariate and bivariate. The results of the study with statistical tests showed that there was a relationship between respondents' knowledge about Tb (p value: 0.001), family support (p value: 0.016) and coping mechanisms (p value: 0.001) with Tb patient compliance. It is recommended that patients who will undergo Pulmonary TB treatment should adhere to a predetermined schedule of taking medication and be able to manage stress well and for the family for the family to provide support and motivation in undergoing treatment and providing all the needs of the patient.Keywords: Family support, Knowledge, Tuberculosis